The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2020
DOI: 10.23873/2074-0506-2020-12-1-28-41
|View full text |Cite
|
Sign up to set email alerts
|

Hyperbaric oxygenation in transplantology

Abstract: The ability to eliminate any form of oxygen debt by transporting oxygen to organs and tissues, by dissolving it in body fluids, brings hyperbaric oxygenation to a new level of application in transplantology. The review discusses the pathophysiological aspects of hyperbaric oxygenation during ischemia and reinfusion, especially when used in transplantology, and also investigations on the use of hyperbaric oxygenation in model experiments and in clinical practice. Analysis of the efficacy of hyperbaric oxygenati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 56 publications
0
1
0
Order By: Relevance
“…In a large number of studies, it was shown that oxygen persufflation has the ability to increase storage time of donor organs [14][15][16]. Hyperoxia facilitates the diffusion of oxygen into the cell, activates oxidative phosphorylation, increases the synthesis of high-energy compound and reduces lactose levels in cells [17]. The combined use of CO and O 2 has proven to be highly effective in prolonging the storage time of warm-blooded animal organs by four to six times when compared to traditional hypothermal preservation techniques using specialized solutions [18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…In a large number of studies, it was shown that oxygen persufflation has the ability to increase storage time of donor organs [14][15][16]. Hyperoxia facilitates the diffusion of oxygen into the cell, activates oxidative phosphorylation, increases the synthesis of high-energy compound and reduces lactose levels in cells [17]. The combined use of CO and O 2 has proven to be highly effective in prolonging the storage time of warm-blooded animal organs by four to six times when compared to traditional hypothermal preservation techniques using specialized solutions [18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%